2002
DOI: 10.5012/bkcs.2002.23.11.1604
|View full text |Cite
|
Sign up to set email alerts
|

SERS of Dithiocarbamate Pesticides Adsorbed on Silver Surface; Thiram

Abstract: In the present work, we studied thiram on silver surface by SERS. Investigations of disulfides with SERS revealed that the molecules undergo a surface reaction on silver, namely easy cleavage of the S-S bond. We believe that the two S atoms of resonance formed from the thiram may be chemisorbed strongly on Ag sol. This resonance form adheres perpendicularly to the Ag surface via the two S atoms, since the δ (CH 3 ) and ν (CN) mode perpendicular to the surface showed strong enhancement. The important roles of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Some methods have been used for the determination of thiram, such as chromatography [51], enzyme linked immunosorbent assay [52] and chemiluminescence analysis [53]. SERS is one effective method to determine the trace residue of thiram [48, 54, 55, 56]. LSPR properties of AgNPs influence remarkably the SERS activity, which has be widely investigated by researchers [40, 41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some methods have been used for the determination of thiram, such as chromatography [51], enzyme linked immunosorbent assay [52] and chemiluminescence analysis [53]. SERS is one effective method to determine the trace residue of thiram [48, 54, 55, 56]. LSPR properties of AgNPs influence remarkably the SERS activity, which has be widely investigated by researchers [40, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6a shows the SERS spectra of thiram with different concentrations (10 −8 M ~ 10 −4 M) obtained from WP-Ag disks. Table 1 displays the details of the assignments of the different SERS bands of thiram [55]. Among the SERS bands, the band at 1381 cm −1 is the strongest, which is the CN stretching mode and symmetric CH 3 deformation mode.…”
Section: Resultsmentioning
confidence: 99%
“…42 Among these issues, thiram (bis-(dimethyl-dithiocarbamoyl) disulfide), a nonsystemic dithiocarbamate fungicide, has been widely used to protect a variety of crops from downy mildew, blight, anthracnose, and cereal smut. 41,43 Due to the lack of environmental awareness and the excessive use of thiram, water and soil are being polluted while much of the residue remains in the surface of fruits and vegetables. In this study, as shown in Fig.…”
Section: Figures 2(a) and 2(b) Were The Top-view And Side-view Fe-semmentioning
confidence: 99%
“…Ultimately, these side effect would bring about many adverse effects upon the promotion of an agricultural economy that strove to achieve sustainable development. 41 Meanwhile, pesticide residues have been concerned as the food safety issues for the public health. 42 Among these issues, thiram (bis-(dimethyl-dithiocarbamoyl) disulfide), a nonsystemic dithiocarbamate fungicide, has been widely used to protect a variety of crops from downy mildew, blight, anthracnose, and cereal smut.…”
Section: Figures 2(a) and 2(b) Were The Top-view And Side-view Fe-semmentioning
confidence: 99%
“…21,22 According to USA Food Standards, the maximum allowable thiram residue in most farm produce is 0.8 ppm. Therefore, a rational and convenient approach to detect thiram with high sensitivity are essential.…”
mentioning
confidence: 99%